2013
DOI: 10.1080/00207594.2012.740566
|View full text |Cite
|
Sign up to set email alerts
|

Blame it on patriarchy: More sexist attitudes are associated with stronger consideration of cosmetic surgery for oneself and one's partner

Abstract: In the present work, we examined associations between oppressive, sexist beliefs and consideration of cosmetic surgery for oneself and also endorsement of cosmetic surgery for one's romantic partner. A total of 554 German-speaking volunteers from the community, mainly in Austria, completed measures of consideration of cosmetic surgery and three measures of sexist attitudes, while a subset of participants in romantic relationships completed a measure of endorsement of cosmetic surgery for their partners along w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The remainder of the articles examined the use of beauty-related practices using self-reports. Ambivalent sexism (mostly HS) was associated with considering cosmetic surgery for oneself and partner (Swami et al, 2013) and with beauty practices (e.g., men’s growing of facial hair or building muscles; Oldmeadow & Dixson, 2016; Swami & Voracek, 2013; Zheng & Zheng, 2015; but cf. Hellmer et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The remainder of the articles examined the use of beauty-related practices using self-reports. Ambivalent sexism (mostly HS) was associated with considering cosmetic surgery for oneself and partner (Swami et al, 2013) and with beauty practices (e.g., men’s growing of facial hair or building muscles; Oldmeadow & Dixson, 2016; Swami & Voracek, 2013; Zheng & Zheng, 2015; but cf. Hellmer et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…In women, signs of aging such as appearance of wrinkles, sagging skin, and uneven skin tone have been linked to lowered female mate value (Buss, 1989; Maestripieri et al, 2014) and thus being at a disadvantage to attract potential mates. It is therefore understandable that for women who want to seek romantic partners, maintaining a youthful appearance is important (Harris, 1994; Swami et al, 2013). In line with this, research has found that older women who engaged in antiaging procedures were rated as more attractive and healthier (Nellis et al, 2017; Tian et al, 2020), which therefore implies that age concealment could prove to be beneficial for older women who are seeking partners.…”
Section: Target Concealment Typementioning
confidence: 99%
“…Practically, the research on the representation of beauty that is not displayed by the Aesthetic Clinic Instagram account provides input that the beauty myth is an attempt of the patriarchal society to control women through their beauty (Bettman 2005;Swami et al 2013). The concept of beauty in today's times teaches two things mainly to women, namely, the adoration of the fear of increasing age and the worship of body weight control.…”
Section: Figurementioning
confidence: 99%
“…Beauty as a feminine representation has been deeply rooted in a culturally wider programmed social system. Every day, women are convinced by beauty myths that increasingly plunge women into the abyss of worshiping beauty (Andreoni and Petrie 2008;Muassomah et al 2021;O'Connor and Gladstone 2018;Swami et al 2013). Beauty or sexuality of women's bodies is always considered as a provocation of sexual harassment against women themselves.…”
Section: Introductionmentioning
confidence: 99%